EFEKTIFITAS METODE COOPERATIVE LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR IPS PADA SISWA MTS AL-FATTAH TUREN MALANG - Zaenal Abidin (El-QUDWAH, 2008)
This research focuses on 1) students’ motivation and achievement in relation with the application of cooperative learning method, 2) the improvement of students learning motivation and achievement using cooperative learning system. The sample collection method is purposive sampling with subject choosing based on research objectives. Data analysis is in the form of experiment. The data analysis is using T test analysis. Based on the data analysis, it is known that the hypothesis that states that the application of cooperative learning method can give effective influence on the improvement of students’ learning motivation and achievement is unacceptable. It means that the application of cooperative learning method cannot give any significant effect on the improvement of students’ learning motivation and achievement. Cooperative learning method still can give a difference that leads to improvement of students’ learning motivation and achievement than before they were given the cooperative learning method or treatment, though the improvement is not very significant. Thereby, although the result of the research still cannot give a good result especially in improving students’ learning motivation and achievement, cooperative learning method still need to be maintained because this method still can give a significant change, and at the same time we have to try to evaluate and to find the solution for the failures.Keyword: Effectivity, Cooperative Learning, Achievement